2022
DOI: 10.1109/access.2022.3205022
|View full text |Cite
|
Sign up to set email alerts
|

In-Vehicle Human Machine Interface: Investigating the Effects of Tactile Displays on Information Presentation in Automated Vehicles

Abstract: Background: Semi-autonomous vehicles still require human drivers to take over when the automated systems can no longer perform the driving task. Objective: The goal of this study was to design and test the effects of six meaningful tactile signal types, representing six driving scenarios (i.e., navigation, speed, surrounding vehicles, over the speed limit, headway reductions, and pedestrian status) respectively, and two pattern durations (lower and higher urgencies), on drivers' perception and performance duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Among the earlier studies on TOR modality, Petermeijer et al observed shorter reaction times for auditory or tactile modality compared to visual modality [12]. Researchers agree that the driver's tactile input channel is the least overloaded during driving, and thus many studies focus precisely on tactile UIs [13]- [15]. Vibrations or different tactile patterns alone generally did not improve reaction time itself, but reduced driver effort and increased situational awareness [16], [17].…”
Section: B Modalities and Stimuli Typesmentioning
confidence: 99%
“…Among the earlier studies on TOR modality, Petermeijer et al observed shorter reaction times for auditory or tactile modality compared to visual modality [12]. Researchers agree that the driver's tactile input channel is the least overloaded during driving, and thus many studies focus precisely on tactile UIs [13]- [15]. Vibrations or different tactile patterns alone generally did not improve reaction time itself, but reduced driver effort and increased situational awareness [16], [17].…”
Section: B Modalities and Stimuli Typesmentioning
confidence: 99%